Relationship of the Musculocutaneous Nerve and Its Twigs to the Coracoid Process: An Operative Exposure - Singh, Hardeep (Orthop J Sports Med, 2020)
BACKGROUND: A musculocutaneous nerve (MCN) injury is a rare complication of the Latarjet procedure. Most of these injuries are neurapraxias and resolve with time; however, permanent injuries can occur. Understanding the anatomy and relationship of the MCN to the coracoid process is essential to prevent injuries. PURPOSE: To provide realistic, in situ–referenced measurements for the Latarjet procedure. STUDY DESIGN: Descriptive laboratory study. METHODS: A total of 12 matched-pair cadaveric specimens (24 fresh-frozen shoulders) were dissected. Coracoid osteotomy was performed, and the MCN and its respective twigs were identified. Measurements were made from the coracoid process to the entry site of the nerve twigs and trunk into the coracobrachialis muscle. RESULTS: Overall, 70.8% of specimens had twigs; however, there was a discrepancy in the presence (41.7%) and number (75.0%) of twigs in the paired specimens. The most proximal twigs were, on average, 33.5 ± 8.1 mm (range, 21.9-47.6 mm) from the coracoid process. The main trunk was, on average, 51.1 ± 14.4 mm (range, 16.7-71.9 mm) from the coracoid process. In 33.3% of specimens, the nerve entered the coracobrachialis at a distance shorter than 5 cm below the coracoid process, and this increased to 91.7% when the twigs were accounted for. CONCLUSION: The previously described safe zone of 5 cm below the coracoid process may not be reliable to protect the MCN or its twigs. Using 3 cm would decrease the chances of damaging a twig or the main trunk. In 33.3% of the specimens, the nerve entered the coracobrachialis at a distance shorter than 5 cm below the coracoid process, and this increased to 91.7% when twigs were accounted for. CLINICAL RELEVANCE: As the Latarjet procedure is an emerging technique, it is essential to be aware of the anatomic structures and the relation between different neural structures to anatomic points of reference. Therefore, the results of this study add significant information for a safe surgical procedure for the majority of patients suffering from shoulder instability.